IMPLEMENTATION OF ART THERAPHY TO MANAGE OF PEOPLE WITH MENTAL DISORDER: LITERATUR REVIEW - Sianturi, Renta; Angraeni Javaluasia; Hana Najla; Laras Andika; Muhammad Fathan; Muhhammad Ricky; Nada sari; Ratna Purnamasari; Siti Meira; Siti Syakira; Vinna Widyanti (STIKes Mitra Keluarga, 2025)
ABSTRACT Introduction: Hallucinations are among the most prevalent psychiatric symptoms encountered in clinical settings and may compromise patient safety if left untreated. This review aims to synthesize evidence on the effectiveness of art therapy for patients experiencing hallucinations. Method: A narrative review was conducted using PubMed, ScienceDirect, and Google Scholar databases. Ten articles published between 2019 and 2024 were selected based on the keywords art therapy, hallucinations, and schizophrenia.Results: Ten studies met the inclusion criteria and were relevant to the objectives of this review. Conclusion: Art therapy demonstrates effectiveness in reducing hallucination symptoms and may be considered a complementary nursing intervention for patients with sensory perception disturbances.